Ventilation Strategies for Deep Energy Renovations of High-Rise Apartment Buildings: Energy Efficiency and Implementation Challenges - Anti Hamburg; Ülar Palmiste; Alo Mikola; Targo Kalamees (Energies)
Ensuring proper indoor air quality in high-rise apartment buildings is a crucial challenge, particularly when upgrading ventilation systems during deep energy renovation of existing buildings. This study evaluates the condition of existing ventilation systems and assesses the performance, cost, and energy efficiency of different mechanical ventilation solutions with heat recovery, including centralized and decentralized balanced ventilation with heat recovery, single-room ventilation units, and mechanical extract ventilation with heat pump heat recovery or without heat recovery. An onsite survey revealed significant deficiencies in existing ventilation systems, such as airtight window installations without dedicated fresh air valves, misaligned and decayed exhaust shafts, and inadequate extract airflow in kitchens and bathrooms. SWOT analyses for each system highlighted their strengths, weaknesses, opportunities, and threats, providing valuable insights for decision-makers. The results indicate that while centralized and decentralized mechanical ventilation with heat recovery enhances energy efficiency and indoor air quality in high-rise multifamily apartment buildings, challenges such as high installation costs, maintenance complexity, and architectural constraints must be addressed. Heat recovery with exhaust air heat pumps is a viable alternative for high-rise apartment buildings when more efficient options are not feasible.